Goal setting and trends in day-care service use by community-dwelling older: A qualitative study using quantitative text analysis - YAMA, Kento; KAMIYA, Kentaro; YAMASHITA, Masashi; MASHIZUME, Yuki (Japanese Journal of Geriatric Therapy, 2022)
【Objective】 This study’s objective was to clarify motivations at the time of service initiation by analyzing the goals of community-dwelling older for first-time use of day-care services in Japan.【Methods】 The target population who used the day-care facility at least once and those who certified as support levels 1-2 (mild disability) and persons eligible for the services. After administering the structured goal setting, we conducted a quantitative text analysis. Relevant terms were extracted using a text-mining method and KH coder. The extracted terms were clustered in a co-occurrence network and inductively categorized and subcategorized. Bubble charts were created for care level, age, level of independence in daily living, and gender.【Results】 Participants of this study were Ninety-six subjects (mean age 79.4 years; 59 women) using day-care services provided by long-term care insurance. The goals were categorized as follows: (1) physical function improvement, (2) walking endurance improvement, (3) independence in the minimum living space necessary to maintain one’s life, (4) going out to the train station, (5) public transportation use, (6) enjoyment of social activities, and (7) exercise-related leisure activities. The bubble charts indicated that the care level and age affected the living space size, while the level of independence in daily living and gender affected the level of social activities.【Conclusion】 The day-care service users mentioned various activities as long-term goals, including social participation, physical functions, and activities aimed at maintaining their range of daily living. This study’s results can help develop effective care prevention targets. 【目的】地域在住高齢者を対象に通所介護サービス初回利用時の目標内容を計量テキスト分析にて解析し，サービス開始時の動機付け因子となる要因を明らかにすることとした。【方法】通所介護を利用している事業対象者・要支援者の96名（平均年齢79.4歳，女性59名）を対象とした。目標設定は構造化された枠組みに沿って行われた後，KH coderを用いたテキストマイニング法にて関連のある用語の抽出と共起ネットワークにて関連性を認めた抽出語をクラスタリングし，カテゴリー，サブカテゴリー分けを実施した。分類したカテゴリーと介護度，年齢，日常生活自立度，性別のバブルチャートを作成した。【結果】目標のカテゴリーとして①身体機能の改善，②歩行の耐久性の向上，③生活水準維持に必要最低限の生活空間での自立，④駅までの外出，⑤公共交通機関の利用，⑥社会活動の獲得，⑦運動関連の余暇活動に分類された。また，バブルチャートにて介護度と年齢は目標の生活空間の広さ，日常生活自立度と性別は目標の社会活動のレベルに一定の関連があることを示した。【結論】社会参加に関連した目標だけでなく，生活範囲の維持等を目的とした身体機能や活動面も目標となり，介護予防対象者へ効果的な動機付けの一助を担える可能性が示唆された。